Stimulasi Kemampuan Motorik Halus Anak Usia 5-6 Tahun Melalui Kegiatan Membatik Ecoprint - Idzni Azhima; Homsani Nasution; Putri Aulia; Nabila Azrina; Insyafiatul Ummi (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Fine motor skills are related to a child's ability to perform activities using small muscle movements such as the fingers and wrists used to perform daily activities such as writing, grasping, buttoning clothes, and other activities. This research is a type of community service research in the form of education delivered to teachers regarding ecoprint batik activities to train fine motor skills, as well as training provided to children aged 5-6 years in the form of batik activities with the ecoprint method. Children's fine motor skills are stimulated from an early age with the aim of training children's independence and readiness to learn. Stimulation of fine motor skills should be done through fun activities and in accordance with the child's age development, one of which is through batik activities with the ecoprint method using the pounding technique, namely by hitting leaves and flowers attached to the cloth. In early childhood, batik activities are carried out using simple tools and materials and paying attention to safety in their implementation. Ecoprint batik aims to train hand-eye coordination, develop manipulative skills, and encourage children's creativity. This community service activity not only trains the fine motor skills of early childhood children, but also provides insight to educators about efforts to develop children's fine motor skills through various fun activities, one of which is through ecoprint batik activities.